Effect of main solid biomass commodities of patula pine on biochar properties produced under gasification conditions (2021)
Wood pellets (WP) and chips (WCH) are the most frequently sold products worldwide to produce bioenergy under thermochemical processes. The effects of the bulk density of patula pine (Pinus patula) WP (555.97 kg/m3) and WCH (151.29 kg/m3), and their gasification conditions were studied on the properties of the produced biochars (BCs). The aim of this study was to generate a good-quality gas fuel (producer gas), as well as a BC with properties that would enable it to be used as a solid biofuel instead of being considered as a byproduct or waste. An atmospheric reverse-downdraft gasifier was used, setting the air flow at 0.12 kg/m2/s for the samples of biomasses studied. With regard to the gasification performance, the temperature inside the reactor was found to increase by 70 % for WP, obtaining a higher cold gas efficiency (51.6 %) in comparison with the efficiency achieved for WCH (36.7 %). Concerning the properties of the BCs, the highest gasification temperature allowed to reach a pellet-derived biochar (WP-BC) with a surface area (BET) larger than that one obtained for the chip-derived biochar (WCH-BC), with 367.33 m2/g and 233.56 m2/g, respectively. Furthermore, the WP-BC heating value was found to be 29.25 MJ/kg, while this parameter for the WCH-BC was 28.36 MJ/kg. It is highlighted the low probability of corrosion and ash fusion occurrence within the reactor when using these biofuels (raw and BCs). Additionally, regarding the pyrolysis kinetics of the raw biomasses, WCH showed a higher reactivity with an activation energy (Eα) of 80.84 kJ/mol in comparison with the Eα value obtained for WP (124.38 kJ/mol).